Análisis de Estimación De Costos Indirectos de Empresas Constructoras en Proyectos Viales. - Vargas Tixi, Luis Miguel (2024)
The purpose of this study is to analyze the methods and tools used by construction companies in Ecuador to estimate indirect costs in road projects. The problem statement aims to determine the factors that influence the lack of precision in the estimation of indirect costs and its impact on the profitability of projects for road construction companies. The purpose of this research is to achieve an accurate and realistic calculation of the percentage of indirect costs so that a project can be planned effectively and it can be guaranteed that the necessary budget is available for its execution. The research methodology project is mixed, using a combination of a quantitative approach with numerical data that demonstrate a percentage of acceptance and the qualitative approach aims to explore the perceptions, experiences and opinions of companies and contractors regarding the calculation of indirect costs. The research population consists of road projects executed through the bidding modality in the analysis period corresponding to fiscal year 2022 within planning zone 3 of the country. A survey was used as a data collection instrument to determine the components of the work that may affect the cost, its essential parameters and the degree of compliance, allowing for optimizing decision making when calculating indirect costs. Based on a frequency analysis of the results obtained in the surveys, an indirect cost model is proposed, considering the items necessary for its formulation. From the results obtained, it is revealed that the indirect cost is not calculated and that, on the contrary, the reference percentage is placed in the contracting processes, since when reviewing the files in the specifications there is no indirect cost calculation report, and this is confirmed since the percentage most used by most contracting entities and contractors is 20%. With the model proposed for calculating indirect costs for each project in the sample, the average of 24.5% was determined, a percentage value that is above 76% of the value assumed by the contracting entities